Studies of endothelial monolayer formation on irradiated poly-l-lactide acid with ions of different stopping power and velocity - Arbeitman, Claudia Roxana (2015)
In this work we study cell viability, proliferation and morphology of bovine aortic endothelial cells (BAEC)cultured on poly-L-lactide acid (PLLA) modified by heavy ion irradiation. In a previous study comparingions beams with the same stopping power we observed an increase in cell density and a better cellmorphology at higher ion velocities. In the present work we continued this study using heavy ions beamwith different stopping power and ion velocities. To this end thin films of 50 µm thickness were irradiated with 2 MeV/u and 0.10 MeV/u ion beams provided the Tandar (Buenos Aires, Argentina) and Tandetron (Porto Alegre, Brazil) accelerators, respectively. The results suggest that a more dense and elongated cell shapes, similar to the BAEC cells on the internal surface of bovine aorta, was obtained for stopping power of 18.2 to 22.1 MeV cm^2 mg^-1 and ion velocity of 2 MeV/u. On the other hand, for low ion velocity 0.10 MeV/u the cells present a more globular shapes.